Building on Capacity Established through US Centers for Disease Control and Prevention Global Health Programs to Respond to COVID-19, Cameroon - Emily Kainne Dokubo; Judith D. Shang; Adama N’Dir; Clement B. Ndongmo; Gordon Okpu; Yasmine Moussa Fadil; Laura Eno Takang; Carrine Angumua; Esther Lyonga; Magdalene Mayer; Tabiayuk Ayukotabe; Tse K. Nkwoh; et al. (Emerging Infectious Diseases, 2022)
The COVID-19 pandemic has highlighted the need for resilient health systems with the capacity to effectively detect and respond to disease outbreaks and ensure continuity of health service delivery. The pandemic has disproportionately affected resource-limited settings with inadequate health capacity, resulting in disruptions in health service delivery and worsened outcomes for key health indicators. As part of the US government’s goal of ensuring health security, the US Centers for Disease Control and Prevention has used its scientific and technical expertise to build health capacity and address health threats globally. We describe how capacity developed through global health programs of the US Centers for Disease Control and Prevention in Cameroon was leveraged to respond to coronavirus disease and maintain health service delivery. The health system strengthening efforts in Cameroon can be applied in similar settings to ensure preparedness for future global public health threats and improve health outcomes.